Tujuan Pendidikan Islam Perspektif Al-Qur'an dan Hadits: (Analisis Q.S Al Baqarah Ayat 201) - Ashhabul Kahfi; Ahmad Saefurridjal; Iskandar Mirza (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
Islamic education when viewed from the perspective of the Qur'an and hadith is the desire for success and happiness in this world and in the hereafter. But how to get it is what must be learned. Islam strongly encourages its adherents to seek knowledge from the time they are in their mother's arms to the grave. Islamic education can change the social attitudes of individuals and the wider community. This research uses a descriptive method of analysis, using a qualitative approach about the verses and hadith that explain the Purpose of Islamic Education, as well as quoting some opinions of scholars of tafsir and hadith experts. As well as various views of modern educational figures in the interpretation of the purpose of education and social change from the perspective of the Qur'an and Hadith. Especially analyzing Q.S Al-Baqarah verse 201. The result is what is called happiness in the world including, favors of knowledge, health, pious women. While happiness in the hereafter includes entering heaven, being kept away from the torment of hellfire, bad women. Islamic education has the aim of social control and internalizing Islamic values. Keywords: Islamic Education; Qur'an Perspective; Q.S Al-Baqarah